Review on the Accelerated and Low-Temperature Polymerization of Benzoxazine Resins: Addition Polymerizable Sustainable Polymers - Lochab, Bimlesh; Monisha, Monisha; Amarnath, Nagarjuna; Sharma, Pratibha; Mukherjee, Sourav; Ishida, Hatsuo (Polymers, 2021)
Due to their outstanding and versatile properties, polybenzoxazines have quickly occupied a great niche of applications. Developing the ability to polymerize benzoxazine resin at lower temperatures than the current capability is essential in taking advantage of these exceptional properties and remains to be most challenging subject in the field. The current review is classified into several parts to achieve this goal. In this review, fundamentals on the synthesis and evolution of structure, which led to classification of PBz in different generations, are discussed. Classifications of PBzs are defined depending on building block as well as how structure is evolved and property obtained. Progress on the utility of biobased feedstocks from various bio-/waste-mass is also discussed and compared, wherever possible. The second part of review discusses the probable polymerization mechanism proposed for the ring-opening reactions. This is complementary to the third section, where the effect of catalysts/initiators has on triggering polymerization at low temperature is discussed extensively. The role of additional functionalities in influencing the temperature of polymerization is also discussed. There has been a shift in paradigm beyond the lowering of ring-opening polymerization (ROP) temperature and other areas of interest, such as adaptation of molecular functionality with simultaneous improvement of properties.